2021
DOI: 10.3389/fonc.2021.711220
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Hellebrigenin and Arenobufagin Against Human Breast Cancer Cells

Abstract: Development of new therapeutic strategies for breast cancer is urgently needed due to the sustained emergence of drug resistance, tumor recurrence and metastasis. To gain a novel insight into therapeutic approaches to fight against breast cancer, the cytocidal effects of hellebrigenin (Helle) and arenobufagin (Areno) were investigated in human estrogen receptor (ER)-positive breast cancer cell line MCF-7 and triple-negative breast cancer cell line MDA-MB-231. Helle exhibited more potent cytotoxicity than Areno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Previous studies conducted on oestrogen receptor (ER)-positive and triple-negative breast cancer cells have demonstrated that hellebrigenin prevents cancer cell proliferation through cell cycle arrest at the G2/M phase, suppressing cell cycle regulators and inducing caspase-mediated apoptosis. 21 Similar findings have been observed in pancreatic and hepatic cancer cells following treatment with hellebrigenin. 15,20 Previous studies investigating the anticancer mode of action of hellebrigenin have shown that both hellebrin and hellebrigenin bind to and inhibit Na+/K+ ATPase with equal potency, leading to activation of caspase-mediated apoptosis of cancer cells.…”
Section: F I G U R E 6 X-linked Inhibitor Of Apoptosis Protein Involv...supporting
confidence: 72%
“…Previous studies conducted on oestrogen receptor (ER)-positive and triple-negative breast cancer cells have demonstrated that hellebrigenin prevents cancer cell proliferation through cell cycle arrest at the G2/M phase, suppressing cell cycle regulators and inducing caspase-mediated apoptosis. 21 Similar findings have been observed in pancreatic and hepatic cancer cells following treatment with hellebrigenin. 15,20 Previous studies investigating the anticancer mode of action of hellebrigenin have shown that both hellebrin and hellebrigenin bind to and inhibit Na+/K+ ATPase with equal potency, leading to activation of caspase-mediated apoptosis of cancer cells.…”
Section: F I G U R E 6 X-linked Inhibitor Of Apoptosis Protein Involv...supporting
confidence: 72%
“…Furthermore, the lack of corresponding receptor targets means that triple-negative breast cancer (TNBC) does not respond to traditional ER-, epidermal growth factor receptor-2 (EGFR)-, and PR-targeted therapies. 21,22 Diphenyl disulfide has two phenyl groups that are connected with a disulfide bond. 13 DPDS derivatives, such as bis[2-(acylamino)phenyl] disulfide, 1,2-bis(4-chlorophenyl) disulfide, 1,2-bis (4-methoxyphenyl) disulfide and 1,2-bis(4-nitrophenyl) disulfide, have been shown to have anticancer effects.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the developing and continuing problems of drug resistance, tumor recurrence, and metastasis, there is a critical need for the development of innovative breast cancer treatment strategies. Furthermore, the lack of corresponding receptor targets means that triple‐negative breast cancer (TNBC) does not respond to traditional ER‐, epidermal growth factor receptor‐2 (EGFR)‐, and PR‐targeted therapies 21,22 . Diphenyl disulfide has two phenyl groups that are connected with a disulfide bond 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Probably one of the most important cardiotonic glycosides found in the composition of Helleborus species is hellebrin, which is found in the largest amount in the species of H. purpurascens [17]. Studies on the antitumor effect of natural compounds, highlighted the role played by hellebrin and its deglycosylated form, hellebrigenin, possesses cytotoxic activity on melanoma [52], pancreatic cancer [53], breast cancer [54], and others. The successful use of these compounds in antitumor treatment is due to the inhibitory activity of the Na+/K+-ATPase complex, which prevents the development of cancer cells' resistance to treatment [52].…”
Section: Discussionmentioning
confidence: 99%